Newly discovered males and new records of the uncommon Neotropical genera Eutabanus Kröber and Myiotabanus Lutz (Diptera: Tabanidae) - Krolow, Tiago Kütter; Bayless, Keith M.; Henriques, Augusto Loureiro (Zootaxa, 2012)
The males of Eutabanus pictus Kröber, Myiotabanus amazonicus Rafael & Ferreira, collected in Amazonas, Brazil, andMyiotabanus muscoideus (Hine), collected in Chiapas, Mexico, a new country record, are described. Species of both genera aresmall horse flies with sarcophagid-like coloration. Diagnoses, illustrations and terminalia characters are presented for males, and illustrations and comments for females. The first key to males for Eutabanus and Myiotabanus is presented.